GAMBARAN AIR BERSIH DAN PERSONAL HYGIENE PENDERITA SKABIES DI WILAYAH KERJA PUSKESMAS SIGALUH 1 - Amanah Cahya Nabila; Dwi Atin Faidah; Joko Malis Sunarno (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2024)
Scabies is an endemic disease in the community caused by Sarcoptes scabiei. Sigaluh I Public Health Center recorded a prevalence of scabies of 319 cases in 2021. The purpose of this study was to describe the provision of clean water and personal hygiene of scabies patient. This research is a descriptive study with a cross sectional approach. The population in this study were patients with scabies in the working area of Sigaluh I Health Center in 2021. Systematic random samplingwas used to gain 76 respondents as samples. The primary data obtained from questionnaires, measurements, and field observations. The results shown that most of the respondents behavior was well in maintaining clean clothes (88.2%), well in maintaining skin cleanliness (96.1%), moderate in maintaining hand and nail hygiene (52.6%), good in maintaining cleanliness genitalia (96.1%), good in maintaining the cleanliness of towels (96.1%), and good in maintaining the cleanliness of the bed and sheets (46.1%). Most of clean water supply condition which used by respondents meet the requirements (96.1%) and had the quality of the water meets the requirements (90.8%). Conclusion of the study was personal hygiene habits mostly on good behavior, most of the sources of clean water supply meet the requirements and the physical quality of water mostly meets the requirements. Respondents were expected to further improve clean and healthy living behavior in order to regarding the factors that cause scabies.